Perlindungan Hukum Bagi Guru Yang Memberikan Sanksi Fisik Dalam Batas Wajar Terhadap Peserta Didik - Ahmad Gazali (Jurnal Penegakan Hukum Indonesia, 2021)
The purpose of this legal research is to find out how the legal arrangements for legal protection for teachers in providing physical sanctions within reasonable limits to students and to determine the impact of criminal cases that ensnare the teaching profession when carrying out their professional duties towards teachers in carrying out their professional duties. This research is a socio-legal research, by collecting primary and secondary data related to legal protection for teachers in providing physical sanctions within reasonable limits, then identified, analyzed and processed descriptively qualitatively.According to the results of this legal research show that: First, the legal protection for teachers in providing physical sanctions within reasonable limits to students in its arrangements has been very well proven bymany laws and regulations and other legal rules that have been ratified, it's just that the application is felt still very lacking considering there are still many legal cases teachers whack teachers. Second, criminal cases that ensnare the teaching profession in carrying out their professional duties cause various impacts on teachers in carrying out their professional duties, including: fear and worry about being polished when giving disciplinary action to students, indifference towards wrongdoing or violation of norms committed students, as well as the criminalization and discrimination carried out by students and parents of students which reduces the professionalism of the teacher so that the teacher's performance is not optimal in the role of educating the administrators of the nation so that it is not achieved from national education goals.